PREVALENCE AND RISK FACTORS OF BRONCHO-OBSTRUCTIVE SYNDROME IN YOUNG CHILDREN - Tursinbekova Xamida Kuanishbaevna; Kdirniyazova Sarbinaz Aybosinovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Relevance of the topic: The article is devoted to the clinical and pharmacological audit of the use of antibiotics in the treatment of broncho-obstructive syndrome (BOS) in premature infants living in the Aral Sea region, using the Republic of Karakalpakstan as an example. Broncho-obstructive syndrome is one of the most common and clinically significant problems among premature infants today. According to a retrospective analysis, the frequency of CF in patients is 1.9% of the total number of children with bronchopulmonary pathology in Tashkent, 1.0% in the Khorezm region and 1.0% in the Republic of Karakalpakstan. Among the social risk factors that have the greatest impact on the development of cystic fibrosis in children, marriage between relatives is considered (26.6%). The main factors aggravating the course of the pathology are: medical and biological factors - complicated pregnancy (91.1%), diseases during pregnancy (73.3%), anemia of I-II degree during pregnancy (100.0%), aggravated premorbid background in the child (anemia of I-II degree - 100.0%, AEE - 91.6%, residual complications of rickets - 63.8%, atopic dermatitis - 91.6%).